Stomata and Transpiration of Droopy Potatoes - Waggoner, Paul E. (1966)
A diploid potato (Solanum tuberosum) mutant called droopy wilts easily. Excised leaves of the mutant lost weight, and hence water, more rapidly and had many more open stomata than leaves of a normal sibling. Further, the stomata of abnormal plants remained open in wilted leaves. When the stomata of the abnormal mutant were closed by a chemical spray, its excised leaves lost water no more rapidly than normal. Thus, the wilting of the mutant must be caused by wide stomata. The wilting of the abnormal leaves and the small dry weight of the plants indicate the advantage of the stomatal hydrostat in the normal plants.